An integrated assessment of the potential of agricultural and forestry residues for energy production in China. Issue 5 (5th January 2016) - Gao, Ji; Zhang, Aiping; Lam, Shu Kee; Zhang, Xuesong; Thomson, Allison M.; Lin, Erda; Jiang, Kejun; Clarke, Leon E.; Edmonds, James A.; Kyle, Page G.; Yu, Sha; Zhou, Yuyu; et al.
Abstract: Biomass has been widely recognized as an important energy source with high potential to reduce greenhouse gas emissions while minimizing environmental pollution. In this study, we employ the Global Change Assessment Model to estimate the potential of agricultural and forestry residue biomass for energy production in China. Potential availability of residue biomass as an energy source was analyzed for the 21st century under different climate policy scenarios. Currently, the amount of total annual residue biomass, averaged over 2003–2007, is around 15 519 PJ in China, consisting of 10 818 PJ from agriculture residues (70%) and 4701 PJ forestry residues (30%). We estimate that 12 693 PJ of the total biomass is available for energy production, with 66% derived from agricultural residue and 34% from forestry residue. Most of the available residue is from south central China (3347 PJ), east China (2862 PJ) and south‐west China (2229 PJ), which combined exceeds 66% of the total national biomass. Under the reference scenario without carbon tax, the potential availability of residue biomass for energy production is projected to be 3380 PJ by 2050 and 4108 PJ by 2095, respectively. When carbon tax is imposed, biomass availability increases substantially. For the CCS 450 ppm scenario, availability of biomass increases to 9002 PJ (2050) and 11 524 PJ (2095), respectively. For the 450 ppm scenario without CCS, 9183 (2050) and 11 150 PJ (2095) residue biomass, respectively, is projected to be available. Moreover, the implementation of CCS will have a little impact on the supply of residue biomass after 2035. Our results suggest that residue biomass has the potential to be an important component in China's sustainable energy production portfolio. As a low carbon emission energy source, climate change policies that involve carbon tariff and CCS technology promote the use of residue biomass for energy production in a low carbon‐constrained world.